Implementation of Employee Skills Module Development with ADDIE Model on Corporate E-Learning - Maulana Okte, Muhamad Ridzki; Yelsha Dwi Pasca (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2025)
This study aims to investigate the development process of instructional materials, the feasibility of the instructional materials, and the outcomes of employees' understanding regarding the development of instructional materials focusing on NDF Car topics for CR positions. The research method employed is research and development (R&D), utilizing the ADDIE model comprising Analysis, Design, Development, Implementation, and Evaluation. Data collection involved documents and e-learning data from the company's CR positions to examine comprehension test results. Validators in this study were Mentors and PICs. The research results indicate that the instructional materials on NDF Car topics for CR positions are deemed suitable for use. This determination stems from the validation conducted by Mentors and PICs, along with comprehension test scores from employees surpassing the minimum threshold (>70). Additionally, e-learning data regarding instructional material usage falls within the categories of relevance, ease of understanding, and usefulness. Hence, it can be concluded that the development of instructional materials using the ADDIE model for NDF Car topics intended for CR positions is deemed appropriate and beneficial for CR employees to utilize.